Interpretation of Nyadran Sonoageng Ritual as the Form of Ritual Communication of Sonoageng Villagers, Nganjuk Regency - Megasari Noer Fatanti; Siti Noer Tyas Tuti (Komunikator, 2020)
This study aims to reveal the meaning of the ritual Nyadran Sonoageng in Nganjuk, East Java. The ritual which has been carried out since 1995 is a traditional communication model (silaturahmi) in the social structure in Nganjuk and a medium of community communication with their ancestors. By using the theoretical framework about ritual communication, the researcher revealed that throughout the process of administering the ritual, there was the involvement of local government to form the discourse of the Nyadran itself. Through a new ethnographic approach that focuses on discovering how people organize their culture in thought and action, the final results of this study indicate that the ritual of Nyadran Sonoageng which initially was a representation of gratitude to God experienced an expansion of meaning as a communication medium and tourism commodity that could generate additional income for residents around Nganjuk Regency. Based on the results of participant observation and in-depth interviews, the researchers obtained a portrait of the meaning of Nganjuk residents on the Nyadran Sonoageng ritual. Interestingly, the active role of the religious leaders, religious leaders/traditional leaders is an essential factor in maintaining the memory of the conception of gratitude to God and ancestors through a performance of the Nyadran Sonoageng ritual.